Segmentacja nabywców jogurtów owocowych - Wilk, Justyna (Segmentation of fruit yoghurt consumers, 2005)
The article presents a segmentation of fruit yoghurt consumers. The k-Means method was used to classify consumers into 3 groups. The classes were separated as regards preferred qualities of chosen product. Segments were characterized by demographic, sociological, economic and geographical features.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 87-96